REPRESENTASI TRADISI DAN BUDAYA LOKAL DALAM SENI RUPA KONTEMPORER YOGYAKARTA - Kasiyan - (FBS UNY, 2009)
This study is aimed at describing three main matters, namely: 1) the representation forms of tradition and local culture dimensions in Yogyakarta contemporary fine arts work representations; 2) the way tradition and local culture dimensions in Yogyakarta contemporary fine art work represented; and 3) factors influencing the strength of tradition and local culture dimensions in the Yogyakarta contemporary fine art work representations as mentioned. This study is a qualitative one with the use of heurmeneutic approach as the main approach underlying the study. The main instrument is the researcher himself, accompanied by the use documentation procedure. The data are in the forms of painting work documentations taken from various exhibition catalogues. The data are analyzed by using the descriptive qualitative technique, containing four steps, namely: data reduction, display, data anlysis, and conclusion making. The results of the study can be described as the following. 1) There is one dominant matter related to the representations of Yogyakarta contemporary fine art representation of the 90s era, that is, the presentation of tradition and Javanese local culture; 2) the deconstructive approach is used to represent the dimensions of tradition and local culture in Yogyakarta contemporary fine arts of the 90s. This approach ends in the use of art representation forms that tend to be critical, metaphorical, and parodical; 3) Factors influencing the strength of these dimensions in Yogyakarta contemporary art representations of the 90s also appear in the 2000s era, that can be divided into two, namely: first, its contact with the international art discourse influences, and second, the Postmodernism paradigm supports that has been widely developing and becoming the current topic in the culture of Indonesian society. Keywords: dimension of tradition, contemporary art, Yogyakarta